Development of Marketing Management Learning Model Based on E-Potofolio in Business Administration Department of Malang State Polythecnic - Mohammad Maskan; Maskur; Achmad Fauzi (Universitas muhammadiyah malang, 2023)
The current lecture approach demands student activity, so that students can build their own knowledge in the learning process. The student center learning (SCL) approach would be more appropriate to the current situation and conditions, where the lecturer acts as a facilitator, mediator and motivator for students in learning because students can learn from various learning sources, such as: textbooks, business experts, the internet, mass media, electronic media or the business environment that surrounds the student's residence. In addition, the assessment of students is also more comprehensive and includes three aspects, namely cognitive, affective and psychomotor. One such learning model is to use the E-Portfolio approach. This is in accordance with the objectives of marketing learning at the Department of Commerce Administration, State Polytechnic of Malang, which was given in semester 1, which emphasized the achievement of the three learning domains, namely: cognitive, affective and psychomotor. The implementation of marketing learning based on E-Portfolio will raise the enthusiasm of lecturers in teaching, because the content and presentation of learning materials involve students actively and go directly to the field. As for students, it will generate attitudes and marketing motivation and be able to understand the focus of the material discussed, because the lecture material is easier to digest because it is based on direct observation and experience in the field. Based on data analyze of research found that research result show E-Portfolio Model can be applied at Marketing Management learning at Commerce Administration, State Polytechnic of Malang.